Role of the Varicella-Zoster Virus gB Cytoplasmic Domain in gB Transport and Viral Egress - Heineman, Thomas C. (American Society for Microbiology, 2002)
To study the function of the varicella-zoster virus (VZV) gB cytoplasmic domain during viral infection, we produced a VZV recombinant virus that expresses a truncated form of gB lacking the C-terminal 36 amino acids of its cytoplasmic domain (VZV gB-36). VZV gB-36 replicates in noncomplementing cells and grows at a rate similar to that of native VZV. However, cells infected with VZVgB-36 form extensive syncytia compared to the relatively small syncytia formed during native VZV infection. In addition, electron microscopy shows that very little virus is present on the surfaces of cells infected with VZV gB-36, while cells infected with native VZV exhibit abundant virions on the cell surface. The C-terminal 36 amino acids of the gB cytoplasmic domain have been shown in transfection-based experiments to contain both an endoplasmic reticulum-to-Golgi transport signal (the C-terminal 17 amino acids) and a consensus YXXφ (where Y is tyrosine, X is any amino acid, and φ is any bulky hydrophobic amino acid) signal sequence (YSRV) that mediates the internalization of gB from the plasma membrane. As predicted based on these data, gB-36 expressed during the infection of cultured cells is transported inefficiently to the Golgi. Despite lacking the YSRV signal sequence, gB-36 is internalized from the plasma membrane; however, in contrast to native gB, it fails to localize to the Golgi. Therefore, the C-terminal 36 amino acids of the VZV gB cytoplasmic domain are required for normal viral egress and for both the pre- and post-Golgi transport of gB.